2014
DOI: 10.1038/cddis.2014.508
|View full text |Cite
|
Sign up to set email alerts
|

A loss of FUS/TLS function leads to impaired cellular proliferation

Abstract: Fused in sarcoma/translocated in liposarcoma (FUS/TLS or FUS) is a multifunctional RNA/DNA-binding protein that is pathologically associated with cancer and neurodegeneration. To gain insight into the vital functions of FUS and how a loss of FUS function impacts cellular homeostasis, FUS expression was reduced in different cellular models through RNA interference. Our results show that a loss of FUS expression severely impairs cellular proliferation and leads to an increase in phosphorylated histone H3, a mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…FUS belongs to the FET family and it encodes a multifunctional RNA-binding protein which is highly associated with tumor progression. The overexpression of FUS can promote growth inhibition and apoptosis of prostate cancer [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…FUS belongs to the FET family and it encodes a multifunctional RNA-binding protein which is highly associated with tumor progression. The overexpression of FUS can promote growth inhibition and apoptosis of prostate cancer [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…54,55 A loss of FUS/ TLS results in decreased cellular proliferation, impaired RNA processing, and increased expression of the closely related Ewing's sarcoma protein EWS. 56 Indeed, the transactivation domains of the TET family of RNA-binding proteins (such as FUS and EWS) may be interchangeable and FUS/ERG fusions have been reported in Ewing's sarcoma patients. 57 We also observed two long antisense RNAs of unknown biologic significance, MAPT-AS1 in Ewing's sarcoma and DLX6-AS1 in synovial sarcoma.…”
Section: Therapeutic Targets In Human Soft Tissue Tumors Ae Sarver Et Almentioning
confidence: 99%
“…Fused in sarcoma/translocated in liposarcoma (FUS/TLS or FUS) is a multifunctional DNA/RNA‐binding protein associated with cancer and neurodegeneration. Some articles revealed that FUS acted as a tumor suppressor and its knockdown increased cell proliferation . Recently, FUS has been shown to interact with a number of lncRNAs in neuron diseases .…”
mentioning
confidence: 99%
“…Some articles revealed that FUS acted as a tumor suppressor and its knockdown increased cell proliferation. (24,25) Recently, FUS has been shown to interact with a number of lncRNAs in neuron diseases. (26) Wang et al (27) reported that FUS could be directed to the regulatory regions of target genes by lncRNA transcripts induced by DNA damage signals.…”
mentioning
confidence: 99%